KEMAMPUAN PENALARAN MATEMATIS SISWA DITINJAU DARI SELF-EFFICACY PADA MATERI RELASI DAN FUNGSI - Addini Nurussalamah; Rina Marlina (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to describe the mathematical reasoning ability of students in terms of their level of self-efficacy. The research sample in this study amounted to 6 students based on the categorization of the level of self-efficacy. The instrument used is a matter of mathematical reasoning ability, interview guidelines, and a self-efficacy questionnaire. This study uses a qualitative approach with a descriptive type of research. The researcher explained the data that had been collected during the research related to the mathematical reasoning ability in terms of the self-efficacy of each student. Based on the research data, the conclusions can be briefly summarized that: (1) students who have high self-efficacy have good mathematical reasoning abilities (2) students who have moderate self-efficacy have fairly good and high mathematical reasoning abilities, (3) students who have moderate self-efficacy Some who have low self-efficacy have a good level of mathematical reasoning ability and some have low mathematical reasoning abilities. So that the level of self-efficacy is not always a reference in the level of students' mathematical reasoning abilities.